PENGARUH SELF-MANAGEMENT TERHADAP MOTIVASI KERJA PERAWAT DALAM MASA PANDEMI COVID-19 DI RUMAH SAKIT SWASTA DI YOGYAKARTA - Astuti, Wahyuningtyas Hendri; Intening, Vivi Retno (Jurnal Kesehatan, 2023)
Introduction: Work motivation is an impulse that grows within a person. Self-management is one way to change behavior, thoughts and feelings. The nurse also mentioned that work motivation tends to decrease during the Covid-19 pandemic. The application of important components in self-management includes problem-solving and decision-making skills that can help nurses in self-management in terms of improving the quality and professionalism of nurses' work. Nurses really need self-management to be able to direct their every action to positive things so that they can increase their work motivation in conditions of increased work stressors due to the Covid-19 Pandemic. Methods: Pre-experimental research design with a one group pretest and posttest approach. The research population is nurses in Yogyakarta private hospital. The sample in this study was 46 respondents with purposive sampling as a sampling technique. This study used a work motivation questionnaire and was given a self-management intervention by online. Results: The most gender is female (87.0%), the most education is D3 (87.0%), the most age is 26-35 years old (45.7%) . Wilcoxon Test results value 0.317 which means 0.317 > = 0.05 so it can be concluded that H0 is accepted and Hα is rejected. Conclusion: There is no effect of self-management on the work motivation of nurses during the Covid-19 pandemic at Yogyakarta private Hsopital. Suggestion: The next researcher is to look for other factors that can affect self-management on nurses' work motivation.